Odpowiedź :
Cześć!
Obliczenia
[tex](x+6)^2=x^2+2\cdot x\cdot6+6^2=\boxed{x^2+12x+36}\\\\(3x-5)^2=(3x)^2-2\cdot3x\cdot5+5^2=\boxed{9x^2-30x+25}\\\\(4x-6)(4x+6)=(4x)^2-6^2=\boxed{24x^2-36}\\\\(\sqrt3+8)^2=(\sqrt3)^2+2\cdot\sqrt3\cdot8+8^2=3+16\sqrt3+64=\boxed{16\sqrt3+67}\\\\(6-2\sqrt2)^2=6^2-2\cdot6\cdot2\sqrt2+(2\sqrt2)^2=36-24\sqrt2+8=\boxed{44-24\sqrt2}[/tex]
Wykorzystane wzory skróconego mnożenia
[tex](a+b)^2=a^2+2ab+b^2\\\\(a-b)^2=a^2-2ab+b^2\\\\(a+b)(a-b)=a^2-b^2[/tex]
Odpowiedź:
a)
(x + 6)^2 = x² + 12x + 36
b)
(3x - 5)^2 = 9x² - 30x + 25
c)
(4x - 6)(4x + 6) = 16x² - 36
d)
(√3 + 8)² = 3 + 16√3 + 64 = 16√3 + 67
e)
(6 - 2√2)² = 36 - 24√2 + 4*2 = 36 - 24√2 + 8 = -24√2 + 44
Szczegółowe wyjaśnienie: